Assessment of Regulation Capacity Requirements for Sending-End Grids Considering Frequency Security - Min Li; Xiaodi Wang; Fang Liu; Xiaming Guo; Dawei Chen; Yunfeng Wen (Energies, 2025)
With the large-scale integration of converter-based renewable energy into power systems and the large-scale construction of HVDC, risks associated with supply–demand imbalance and post-contingency frequency instability of sending-end power grids have significantly escalated. This paper proposes a novel method for evaluating the regulation capacity requirements of sending-end grids, addressing both normal-state power balance and post-disturbance frequency security. In normal states, multiple flexible metrics that can quantify the supply–demand imbalance trend are introduced. Then, thermal power units and energy storage serve as the benchmark to quantify the specific capacity requirements. For post-contingencies, frequency security metrics are derived based on the system frequency dynamic model with synchronous generators, renewable energy, and energy storage. The derived frequency security metrics can quantify the credible frequency regulation capacity required to ensure system stability under a predefined disturbance. A multi-objective capacity requirement assessment model for both the normal state and the post-contingency frequency regulation is ultimately formulated to determine the minimum capacity requirements. The effectiveness of the proposed evaluation method is verified using the numerical simulation based on a practical sending-end grid.